2009
DOI: 10.1016/j.bcp.2009.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Differential interactions of the catalytic subunits of adenylyl cyclase with forskolin analogs

Abstract: The diterpene forskolin (FS) binds to, and activates, mammalian membranous adenylyl cyclase (AC) isoforms I–VIII. Diterpenes without C1-OH group do not activate ACs. The C1-OH group forms a hydrogen bond with the backbone oxygen of Val506 of the C1 catalytic subunit of AC (isoform V numbering). To better understand the mechanism of AC activation we examined the interactions of FS and eight FS analogs with purified catalytic AC subunits C1 (AC V) and C2 (AC II) by fluorescence spectroscopy, using 2′,3′-O-(N-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 22 publications
(57 reference statements)
0
40
0
Order By: Relevance
“…These compounds may be useful for future crystallographic and fluorescence spectroscopy studies with sGCa 1 b 1 . By analogy to previous studies with mAC VC1:IIC2 (Mou et al, 2005(Mou et al, , 2006Pinto et al, 2009Pinto et al, , 2011Suryanarayana et al, 2009), such biophysical studies with sGCa 1 b 1 are expected to provide major insights into the molecular mechanisms underlying sGC regulation by NO, sGC activators, and sGC stimulators (Daiber et al, 2010;Derbyshire and Marletta, 2012;Follmann et al, 2013;Stasch and Evegenov, 2013). In fact, Busker et al (2014) has recently reported on the application of (M)ANT-nucleotides for monitoring conformational changes in sGC upon activation.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These compounds may be useful for future crystallographic and fluorescence spectroscopy studies with sGCa 1 b 1 . By analogy to previous studies with mAC VC1:IIC2 (Mou et al, 2005(Mou et al, , 2006Pinto et al, 2009Pinto et al, , 2011Suryanarayana et al, 2009), such biophysical studies with sGCa 1 b 1 are expected to provide major insights into the molecular mechanisms underlying sGC regulation by NO, sGC activators, and sGC stimulators (Daiber et al, 2010;Derbyshire and Marletta, 2012;Follmann et al, 2013;Stasch and Evegenov, 2013). In fact, Busker et al (2014) has recently reported on the application of (M)ANT-nucleotides for monitoring conformational changes in sGC upon activation.…”
Section: Discussionmentioning
confidence: 82%
“…These nucleotides bind to the catalytic site of VC1:IIC2, and the TNP or (M)ANT group projects into a pocket adjacent to the catalytic site, conferring high affinity of the ligands for mACs and stabilizing inactive mAC conformations between the open and closed states (Mou et al, 2005(Mou et al, , 2006Hübner et al, 2011;. Hydrophobic interactions of the TNP-or (M)ANT-nucleotides were also explored to monitor conformational changes in mACs by fluorescence spectroscopy, providing major new insights into the dynamics of enzyme regulation (Mou et al, 2005(Mou et al, , 2006Pinto et al, 2009Pinto et al, , 2011Suryanarayana et al, 2009;Hübner et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that we have found that 1,9-dideoxyforskolin, an inactive analog of forskolin (Pinto et al, 2008(Pinto et al, , 2009, also inhibited ET A R-operated Ca 2ϩ influx via TRPC6 (Supplemental Fig. S3).…”
Section: Pka-mediated Inhibition Of Et a R-induced Ca 2؉ Entry Via Trmentioning
confidence: 90%
“…S3). Because it is well known that forskolin can exhibit pleiotropic effects in an AC-independent manner (Laurenza et al, 1989), we examined the effect of 1,9-dideoxyforskolin, an inactive analog of forskolin as a negative control (Pinto et al, 2008(Pinto et al, , 2009, on the ET A R-operated Ca 2ϩ influx via TRPC6. We were surprised to find that 10 M 1,9-dideoxyforskolin as well as 10 M forskolin inhibited the TRPC6-mediated Ca 2ϩ entry (Supplemental Fig.…”
Section: Pka-mediated Inhibition Of Et a R-induced Ca 2؉ Entry Via Trpc6mentioning
confidence: 99%
“…Although forskolin is an AC activator, inhibitors that target the forskolin binding site have been identified (Pinto et al, 2009;Erdorf et al, 2011). Since our virtual screening focused only on the ATP site, we wanted to rule out that SQ22,536 and the other molecules that inhibited AC activity do not exert their actions through interactions with the forskolin pocket.…”
Section: Ac5 Inhibitorsmentioning
confidence: 99%